Construct validation of 17-item Utrecht university work engagement scale amongst the white collar employees of Malaysian universities - Ahmed, Umar; Abdul Majid, Abdul Halim; Mohd Zin, Md. Lazim (Human Resource Management Academic Research Society, 2016)
Primarily, the study investigated the psychometric properties of UWES work engagement scale were assessed in the context of education sector of Malaysia. Staff members from the two public sector universities in the Kedah state were sampled whereby, 205 questionnaires were distributed that resulted in 180 appropriate responses for final data analysis.The results have indicated towards satisfactory level of internal consistency reliability, convergent; as well as discriminant validity.The structural equation modeling has highlighted higher order stability for work engagement ranging between 0.803 and 0.838.The findings henceforth, conclude that UWES-17 is construct is robust in assessing work engagement among the while collar employees working in the education sector of Malaysia.